Pengaruh Pelatihan, Disiplin dan Penghargaan terhadap Kinerja Karyawan PT Bank Sinarmas di Kabupaten Bekasi - Suwandi Suwandi; Grecia Sutanti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
Human resources in an organization will play an effective role when driven and controlled by a workforce who has achievements. The most important factor in supporting the success of an organization or company is employee performance. High productivity will be very beneficial for both employers and employees, especially for their welfare. Various efforts that can be taken by a company to develop its human resources to encourage progress for the company are using conducting training, increasing discipline, and giving rewards to employees. The purpose of this study was to determine the effect of training, discipline, and rewards on employee performance. The sample in this study were all Sinarmas Banks in the Bekasi district, amounting to 65 people. Statistical analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS software. The results in this study explain that there is an effect of training on employee performance, the influence of discipline on employee performance, and the influence of reward on employee performance.